Folding of proteins in presculpted free energy landscape - Hung, Nguyen Ba; Hoang, Trinh Xuan (Communications in Physics, 2013)
Recent studies of the tube model of protein have indicated that the free energy landscape of proteins is presculpted by symmetry of the protein backbone and geometrical constraints played by the hydrogen bonds. In this study, we investigate the role of amino acid sequences in the folding of proteins. We consider two models that are differed by sequence specificity: the tube HP model with hydrophobic (H) and polar (P) sequences, and the tube Go model with native-centric contact potentials. Monte Carlo simulations are carried out for two sequences of length of 48 amino acids, whose ground states are a three-helix bundle and a GB1-like structure. The results show that folding inthe Go model is more cooperative than in the HP model. In the HP model the collapse transition and the folding transition are separated, whereas in the Go model the two transitions coincide.